Understanding the Impacts of Surgical Drains on Postoperative Pain and Quality of Life - Goutam K. Gadiraju, BS; Matthew R. Prospero, BS; Finn Tobias, BA; Andrew J. Malek, BS; Erik Reiche, MD; Justin M. Broyles, MD, MPH (Plastic and Reconstructive Surgery, Global Open)
Background:. Surgical drains are commonly used in breast surgery and breast reconstruction for seroma prevention. Although many surgeons are aware that surgical drains can cause considerable discomfort to patients, less is understood about the specific impacts of drains on postoperative pain and quality of life (QOL). Methods:. A cross-sectional survey was conducted among patients at our institution who had previously undergone mastectomy or breast reconstruction procedures to better understand patients’ experiences with surgical drains. Patients were asked to report their attitudes toward a series of QOL statements and rate postoperative pain using numeric pain scales. Pair-wise analysis was used to identify predictors of responses. Results:. A total of 203 complete responses were recorded. Increased pain scale ratings for pain at the body wall, incision site, and drain entry site were significantly associated with drain duration at 2–3 weeks or longer (P < 0.05). Notably, 84.7% of patients reported that drains increased the difficulty of completing daily tasks. Most patients (66.0%) reported negative impacts on mood, and 37.0% reported apprehension toward undergoing future procedures that may require drains. Most patients (65.0%) also expressed that they would prefer to receive care from institutions that utilize improved alternatives to standard drains. Conclusions:. Surgical drains cause substantial discomfort to most patients and exert several negative impacts on QOL. In addition to limiting drain use wherever possible, innovations in technique and the development of alternatives to existing drains may offer patients a less painful, improved postoperative recovery experience.